Cistite hemorrágica induzida por ciclofosfamida e ifosfamida: envolvimento de citocinas e oxido nítrico na patogênese da lesão induzida por ciclofosfamida - Gomes, Teresa Neuma Albuquerque (1995)
Hemorragic cystitis (HC) develops as an adverse side effect of the clinicai use of cyclophosphamide (CYP) and ifosfamide (IFS). In the present study, the involvement of cytokines (TNF-a, IL- IL-6 and IL-8) and nitric oxide (NO) in the inflammatory events of HC was evaluated. HC was induced by injecting CYP and IFS (100-400 mg/Kg, i.p.) in male Swiss mice. The animais were sacrificed after 6,12,24,48 and 72 hours and their urinary bladders were evaluated for wet weight and vascular leakage by Evans blue leakage method (25 mg/Kg, i.v„, 1 hour before sacrifice), as well as histopathological analysis using Gray's criteria (urothelial shedding, ulcer, edema, congestion, hemorrhage and leukocyte infiltration). It was observed that CYP and IFS induced, in a dose and time-dependent manner, a significant increase in vascular leakage and wet bladder weight, with maximum effect at 12 hours, when severe histopathological alterations occurred. The use of 2-sodium mercaptoethanosulfonate (mesna)- a proven, clinically-efficient uroprotector - conferred urinary bladder protection against HC induced by both CYP and IFS. The pretreatment of animais with antisera against TNF-a significantly diminished the inflammatory events of HC induced by CYP, in 6 and 12 hour periods. Pretreatment with antisera against IL- IP, IL-6 and IL-8, álso resulted in the attenuation of the lesion, but the result was significant only at 12 hour period, thus suggesting that TNF-a participated in the early stages of inflammatory events occurring in HC.